2008
DOI: 10.1128/jb.01140-07
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosaPqsA Is an Anthranilate-Coenzyme A Ligase

Abstract: Pseudomonas aeruginosa is an opportunistic human pathogen which relies on several intercellular signaling systems for optimum population density-dependent regulation of virulence genes. The Pseudomonas quinolone signal (PQS) is a 3-hydroxy-4-quinolone with a 2-alkyl substitution which is synthesized by the condensation of anthranilic acid with a 3-keto-fatty acid. The pqsABCDE operon has been identified as being necessary for PQS production, and the pqsA gene encodes a predicted protein with homology to acyl c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
133
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(142 citation statements)
references
References 56 publications
4
133
0
5
Order By: Relevance
“…Interestingly, the halogenated anthrnilate analogues were also shown to increase the osmosensitivity of a range of bacterial pathogens in a QS-independent manner (158), suggesting that these compounds may have broader-range therapeutic potential than originally anticipated. The identification of PqsA as the carboxylic acid-CoA ligase responsible for activation of anthranilate has now provided an additional means by which to screen for inhibitors of PQS production (159). Initial experiments have shown that PQS synthesis inhibitors can be either substrates or nonsubstrates of PqsA, and thus it appears that either competitive inhibition of anthranilate binding or inhibition of downstream enzymes may be a successful approach for PQS quorum quenching (159).…”
Section: Inhibition Of Pqs Productionmentioning
confidence: 99%
“…Interestingly, the halogenated anthrnilate analogues were also shown to increase the osmosensitivity of a range of bacterial pathogens in a QS-independent manner (158), suggesting that these compounds may have broader-range therapeutic potential than originally anticipated. The identification of PqsA as the carboxylic acid-CoA ligase responsible for activation of anthranilate has now provided an additional means by which to screen for inhibitors of PQS production (159). Initial experiments have shown that PQS synthesis inhibitors can be either substrates or nonsubstrates of PqsA, and thus it appears that either competitive inhibition of anthranilate binding or inhibition of downstream enzymes may be a successful approach for PQS quorum quenching (159).…”
Section: Inhibition Of Pqs Productionmentioning
confidence: 99%
“…Farnesol, a common sesquiterpene produced by many organisms, was found to inhibit PQS production in P. aeruginosa, although the high concentrations required may hamper in vivo applications (39). Synthetic anthranilate derivatives (23,36,116) have been developed and have shown promising results in a P. aeruginosa mouse infection model (116). In parallel, Fetzner and coworkers reported PQS-degrading activity by conversion of PQS to N-octanoylanthranilic acid by the dioxygenase Hod (1H-3-hydroxy-4-oxoquinaldine 2,4-dioxygenase) of Arthrobacter nitroguajacolicus (162).…”
Section: Targeting Bacterial Signalingmentioning
confidence: 99%
“…PqsA was previously reported to be required for lysis of Staphylococcus aureus, resulting in increased iron availability to P. aeruginosa (30). The specific mechanism for this activity remains unclear and is likely to be multifactorial, as anthraniloyl-CoA can serve as the precursor for at least 55 unique alkylquinolone (AQ) molecules (29,31). One of these, 2-heptyl-4-hydroxyquinoline N-oxide (HQNO), is an N-oxide ubiquinone that inhibits growth of Gram-positive bacteria, including S. aureus (32)(33)(34)(35)(36).…”
mentioning
confidence: 99%
“…PQS production is initiated by PqsA, a coenzyme ligase that converts anthranilate to anthraniloyl coenzyme A (anthraniloylCoA) (29). PqsA was previously reported to be required for lysis of Staphylococcus aureus, resulting in increased iron availability to P. aeruginosa (30).…”
mentioning
confidence: 99%